The study on factors that contributes to the learning styles among Bachelor in Information Studies students in UiTM Kedah / Noor-Ishi Masayu Hamzah - Hamzah, Noor-Ishi Masayu (Faculty of Information Management, 2010)
Learning style is a method use by individual so they can practice and fell comfort with it towards of their learning Moreover, learning style is a cluster of psychological traits that determine how a person perceives, interact with, and responds emotionally to learning environments. In chapter one, background of the topic, statement of problem, purpose of the study, objectives of the study, hypothesis of the study, significance of the study, definition of terms, scope of the study, and limitations of the study has been discussing. While for chapter two, there are related terms that been evaluate in literature review. Lastly, in chapter three, in methodology, research design, data collection method, the questionnaire, operational definitions of all variables and terms, reliability and validity of instruments, and data analysis is being identify. Findings that related to the study has been analysis and been identify. The researcher indicated several recommendations related to the factor of learning styles in the chapter 5.